1987
DOI: 10.1159/000163392
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Expression in Human Chorionic Villi

Abstract: The physicochemical properties and electrophoretic mobility of different isoforms of alkaline phosphatase were studied in chorionic villi. Based on selective inactivation and inhibition studies (thermal stability, inactivation by urea, EDTA and L(+)ascorbic acid and L-amino acid inhibition), evidence was obtained for the existence of two distinct types of alkaline phosphatase in trophoblast cells. One type is peculiar to chorionic villi while the other is also found in term placenta. Both show two isoforms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Fig. ( 4), (10) Illustrates the inhibition of EDTA for E.coli ALP activity.Urea inhibits the activity of the enzyme via blocking the active site.This result confirms with the results arrived at by [45].They found that the activity of ALP extracted from human choronic villi is being inhibited by Urea,EDTA , L-(+)ascorbic acid and Lamino acid. Fig.…”
Section: Mercaptoethanoland Poly Vinylpyrollidone(pvp)supporting
confidence: 92%
“…Fig. ( 4), (10) Illustrates the inhibition of EDTA for E.coli ALP activity.Urea inhibits the activity of the enzyme via blocking the active site.This result confirms with the results arrived at by [45].They found that the activity of ALP extracted from human choronic villi is being inhibited by Urea,EDTA , L-(+)ascorbic acid and Lamino acid. Fig.…”
Section: Mercaptoethanoland Poly Vinylpyrollidone(pvp)supporting
confidence: 92%
“…Trp partially inhibited the tumor-specific ALP (TSALP). These two aromatic amino acids have previously been found to inhibit laryngeal tumor ALP and other oncofetal ALPS (13,14,17,18) Leu inhibited ALP of tumor cells and blood vessels but not that of the interstitial fibrous tissue. The difference in the percentage inhibition between that caused by Leu and that affected by Phe suggests that the vascular ALP comprises about 50% of the total pool and thus makes the major contribution to the pool.…”
Section: Discussionmentioning
confidence: 91%
“…Phe sensitivity and heat stability are characteristics of the Regan and Nagao isoenzymes (6,20,21). Trp, which partially inhibited the TSALP, has been found to inhibit other heat-resistant ALPS (12,13). Leu, which inhibits the Nagao but not the Regan isoenzyme (23,24), profoundly inhibited the TSALP.…”
Section: Discussionmentioning
confidence: 99%
“…19,[29][30][31][32] Exosomes' functional role in pre-eclampsia, gestational diabetes pathogenesis, placental dysfunctions, and their biomarker potentials has been well reported. [33][34][35][36][37][38][39][40] This was made possible partly due to the presence of placental alkaline phosphatase (PLAP), an enzyme present in placental trophoblast cells 41 and expressed on the membrane of trophoblast-derived exosomes. Tagging PLAP has been used as a method of isolating and characterizing exosomes which facilitated studying them as a snapshot of placental function.…”
mentioning
confidence: 99%